PENGARUH KONSENTRASI KEPEMILIKAN DAN KARAKTERISTIK DEWAN TERHADAP KINERJA PERUSAHAAN SEKTOR MANUFAKTUR DI BEI PERIODE 2012-2016 - Aprilia Pratiwi; Deddy Marciano; Arif Herlambang (CALYPTRA, 2018)
This research aim to analyze factors which affect firm performance.Variables which use are ownership concentration, board size, board professionals, and board independents. And also, interaction variable which are ownership concentration x board size, ownership concentration x board professionals, andownership concentration x board independents. This research use quantitative approach by using multiple linier regression on 5 model, model 1 is the base line model and model 2-5 are the interaction models.. The sample of this research is the industrial manufacturing company that listed in BEI (Bursa Efek Indonesia) for period of 2012-2016. Final samples which are used in this research are equal to 109 observation.